Four distal root canals in a two-rooted permanent mandibular first molar: Report of a rare case, its incidence, and literature review - Urvashi M Ujariya; Foram H Patel; Rajendra P Bharatiya; Anjali K Kothari (Wolters Kluwer Medknow Publications, 2022)
Understanding root canal anatomy and its variations is an essential part of the success of endodontic treatment. This case report represents an extremely rare occurrence of four distal root canals in a two-rooted mandibular first molar (MFM). Nonsurgical endodontic treatment of MFM was performed with the aid of the dental operating microscope and ultrasonic troughing tips. PubMed database (www.ncbi.nim.nih.gov/pubmed) was searched for relevant articles using specific search terminologies for conducting the literature review. Data extraction was performed in relation with the inclusion and exclusion criteria provided in the study. Quantitative data synthesis was performed. Only four cases (including the present case) of four distal root canals in two-rooted MFMs have been reported in dental literature. Among these, three cases were reported in the Indian population. The overall incidence of four canals in a distal root of two-rooted MFMs is 0.09% according to clinical/laboratory studies. The most common distal root canal configurations of two-rooted MFMs found in clinical/laboratory studies were Vertucci type I (68.15%) followed by type II (37.6%) and type III (35.08%). A meticulous understanding of the anatomical variations, preoperative awareness, and intraoperative care to identify the landmarks of usual as well as any unusual anatomy of the root canal system will help to increase the rate of clinical success.